Kangaroo Method: potentialities, barriers and difficulties in humanized care for newborns in the Neonatal ICU - Susian Cássia Liz Luz; Marli Terezinha Stein Backes; Rosiane da Rosa; Eudinéia Luz Schmit; Evangelia Kotzias Atherino dos Santos (Associação Brasileira de Enfermagem, 2021)
ABSTRACT Objective: To identify the potentialities, barriers and difficulties for the implementation of humanized care from the perspective of the Kangaroo Method. Methods: Integrative literature review with a time cut from 02/01/2015 to 06/01/2019, totaling ten articles in the final sample. Results: The findings were categorized into two categories: Potentialities for humanized care from the perspective of the Kangaroo Method; Barriers or difficulties to the implementation of the Kangaroo Method. Several potentialities for humanized care allied to technology and continuing education were identified, as well as several barriers to the implementation of the Kangaroo Method, such as lack of physical space, lack of professionals and team training, lack of knowledge, lack of adherence and professional demotivation. Final considerations: There are still few studies that address the potentialities, barriers and difficulties for the implementation of humanized care from the perspective of the Kangaroo Method, and most of those included in this review were conducted in Brazil and present a qualitative approach.